2021
DOI: 10.3390/ani11030686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Restriction and Subsequent Realimentation on Body Composition, Gut Microbiota and Metabolite Profiles in Weaned Piglets

Abstract: The objective of this study was to evaluate the effects of protein restriction and subsequent protein realimentation on the body composition, gut microbiota and metabolite profiles of piglets. Fifty weaned piglets were randomly assigned to two treatments: a normal protein (NP) group (20% crude protein (CP)) or a low protein (LP) group (16% CP) with five animals per pen and five pens per group. Treatment diets were fed for 14 d during the protein restriction phase, and then all pigs were fed the same nursery di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 78 publications
2
10
1
Order By: Relevance
“…Low protein diet was speculated to increase intestinal metabolic activity by the functional prediction on gut microbial flora of pigs fed different protein content diets because genes in intestinal microorganisms at different protein levels are mainly enriched in the "metabolism pathway" (Wang D. et al, 2020). Differences of gut microbiota and its metabolites in piglets induced by protein restriction were demonstrated, and low protein diet was confirmed to decrease mainly the concentrations of biogenic amines, phenolic and indole compounds, and acetate and total SCFA (Yu et al, 2017;Hou et al, 2021). Similarly, we also found an abundant decrease of histamine, phenolic and acetate compounds, etc., in growing-finishing pigs fed low protein diet.…”
Section: Discussionmentioning
confidence: 99%
“…Low protein diet was speculated to increase intestinal metabolic activity by the functional prediction on gut microbial flora of pigs fed different protein content diets because genes in intestinal microorganisms at different protein levels are mainly enriched in the "metabolism pathway" (Wang D. et al, 2020). Differences of gut microbiota and its metabolites in piglets induced by protein restriction were demonstrated, and low protein diet was confirmed to decrease mainly the concentrations of biogenic amines, phenolic and indole compounds, and acetate and total SCFA (Yu et al, 2017;Hou et al, 2021). Similarly, we also found an abundant decrease of histamine, phenolic and acetate compounds, etc., in growing-finishing pigs fed low protein diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Hou et al and our group revealed that protein succedent realimentation was an effective way to rescue the loss of growth performance caused by the prior protein restriction ( 4 , 10 ). These results demonstrated that protein restriction and succedent realimentation improved feed conversion, protein deposition, and intestinal health in weaning piglets ( 4 , 10 ).…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies by Hou et al and our group revealed that protein succedent realimentation was an effective way to rescue the loss of growth performance caused by the prior protein restriction ( 4 , 10 ). These results demonstrated that protein restriction and succedent realimentation improved feed conversion, protein deposition, and intestinal health in weaning piglets ( 4 , 10 ). Our group revealed that weaning piglets achieve compensatory growth after protein restriction and succedent realimentation through a mechanism closely related to hepatic growth hormone (GH)/insulin-like growth factors (IGF-1) signaling axis activation ( 11 ).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The procedure of microbial metabolite measurement as our previously describe [19] using Vanquish UHPLC system (Thermo Fisher) coupled with an Orbitrap Q Exactive series mass spectrometer (Thermo Fisher). Brie y, the homogenate of grounded colonic digesta was centrifuged.…”
Section: Microbial Metabolite Measurementmentioning
confidence: 99%